Akuntabilitas dan transparansi pengelolaan bantuan langsung tunai dana desa dalam pencapaian good governance - Juwita Nur Radeana; Driana Leniwati; Ahmad Juanda; Agustin Dwi Haryanti (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2024)
This research aims to understand the management of Village Fund Cash Transfer to establish good governance, based on phenomena that occurred in Sentul Village, Pasuruan Regency. This study analyzes the Village Fund Cash Transfer utilizing the interpretive paradigm and qualitative approach. Data is obtained by conducting in-depth interviews with the local authority and Sentul local inhabitants of Sentul Village, who were key informants. This research found that Village Fund Cash Transfer is interpreted as funds that must be accounted for, social safety nets, and relationships. The distribution of village fund cash transfers should comply with the concept of good governance to achieve a fair government. Empirically, in a broader sense, the Village Fund Cash Transfer is not only defined as aid for the poor, but also as funds that must be accounted for and a relationship of trust that must be maintained. This research focuses on analyzing the accountability and transparency of Village Fund Cash Transfer in Sentul Village to achieve good governance.